Analysis of Weaknesses and Recommendations for IT Governance Development in SIGAP at the Bureau of Leadership Administration, Regional Secretariat of North Sumatra Province - Efriansyah Putra Bahari Barus; Andysah Putera Utama Siahaan; Muhammad Amin (Jurnal Sistem Komputer dan Informatika (JSON), 2026)
The implementation of effective information technology governance is necessary to support the quality of digital-based personnel administration services at the Bureau of Leadership Administration of the Regional Secretariat of North Sumatra Province. The problem faced is that the capability level of information technology governance in the Salary and Employe Appreciation Information System (SIGAP) is not yet known, so an evaluation is needed to identify areas that require improvement. This research aims to evaluate the capability level of information technology governance in the Employe Salary and Appreciation Information System (SIGAP) using the COBIT 2019 framework. The method used is descriptive quantitative with data collection techniques thru questionnaires, interviews, observations, and document studies. The evaluation was conducted on the domains EDM01, EDM02, EDM03, EDM04, EDM05, APO02, APO03, APO07, APO11, and APO14. The research results show that seven domains, namely EDM01, EDM02, EDM03, EDM04, APO02, APO03, and APO07, achieved Capability Level 3 (Established Process), while EDM05, APO11, and APO14 are at Capability Level 2 (Managed Process). Gap analysis shows that all domains still have a gap of one level against the set target. As a corrective solution, it is recommended to enhance process performance measurement, stakeholder engagement, quality management, data governance, and the development of SIGAP digital services to support the continuous improvement of information technology governance.